The role of delocalization and excess energy in the quantum efficiency of organic solar cells and the validity of optical reciprocity relations - Felekidis, Nikolaos; Melianas, Armantas; Kemerink, Martijn (The journal of physical chemistry letters, 2020)
The photon energy dependence of long-range charge separation is studied for two prototypical polymer:fullerene systems. The internal quantum efficiency (IQE) of PCDTBT:PC61BM is experimentally shown to be independent of the excitation energy. In contrast, for TQ1:PC71BM the IQE is strongly energy-dependent for excitation energies close to charge transfer (CT) electroluminescence peak maximum while it becomes energy-independent at higher excitation energies. Kinetic Monte Carlo simulations reproduce the experimental IQE and reveal that the photon energy-dependence of the IQE is governed by charge delocalization. Efficient long-range separation at excitation energies corresponding to the CT electroluminescence peak maximum or lower requires an initial separation of the hole-electron pair by ∼4-5 nm, whereas delocalization is less important for charge separation at higher photon energies. Our modeling results suggest that a phenomenological reciprocity between CT electroluminescence and external quantum efficiency does not necessarily prove that commonly employed reciprocity relations between these spectra are valid from a fundamental perspective.